(untitled) (Clinics, 2021)
OBJECTIVES: This observational, cross-sectional study based aimed to test whether heart failure (HF)-disease management program (DMP) components are influencing care and clinical decision-making in Brazil. METHODS: The survey respondents were cardiologists recommended by experts in the field and invited to participate in the survey via printed form or email. The survey consisted of 29 questions addressing site demographics, public versus private infrastructure, HF baseline data of patients, clinical management of HF, performance indicators, and perceptions about HF treatment. RESULTS: Data were obtained from 98 centers (58% public and 42% private practice) distributed across Brazil. Public HF-DMPs compared to private HF-DMP were associated with a higher percentage of HF-DMP-dedicated services (79% vs 24%; OR: 12, 95% CI: 94-34), multidisciplinary HF (MHF)-DMP [84% vs 65%; OR: 3; 95% CI: 1-8), HF educational programs (49% vs 18%; OR: 4; 95% CI: 1-2), written instructions before hospital discharge (83% vs 76%; OR: 1; 95% CI: 0-5), rehabilitation (69% vs 39%; OR: 3; 95% CI: 1-9), monitoring (44% vs 29%; OR: 2; 95% CI: 1-5), guideline-directed medical therapy-HF use (94% vs 85%; OR: 3; 95% CI: 0-15), and less B-type natriuretic peptide (BNP) dosage (73% vs 88%; OR: 3; 95% CI: 1-9), and key performance indicators (37% vs 60%; OR: 3; 95% CI: 1-7). In comparison to non- MHF-DMP, MHF-DMP was associated with more educational initiatives (42% vs 6%; OR: 12; 95% CI: 1-97), written instructions (83% vs 68%; OR: 2: 95% CI: 1-7), rehabilitation (69% vs 17%; OR: 11; 95% CI: 3-44), monitoring (47% vs 6%; OR: 14; 95% CI: 2-115), GDMT-HF (92% vs 83%; OR: 3; 95% CI: 0-15). In addition, there were less use of BNP as a biomarker (70% vs 84%; OR: 2; 95% CI: 1-8) and key performance indicators (35% vs 51%; OR: 2; 95% CI: 91,6) in the non-MHF group. Physicians considered changing or introducing new medications mostly when patients were hospitalized or when observing worsening disease and/or symptoms. Adherence to drug treatment and non-drug treatment factors were the greatest medical problems associated with HF treatment. CONCLUSION: HF-DMPs are highly heterogeneous. New strategies for HF care should consider the present study highlights and clinical decision-making processes to improve HF patient care.